THE ANALYSIS OF SOCIAL PROTECTION EXPENDITURE OF ROMANIA BY FUNCTIONS ACCORDING TO THE EUROPEAN UNION METHODOLOGY - OANA DOBRE-BARON (Annals of the University of Petrosani: Economics)
For Romania, the status of full member of the European Union created obligations, but especially the need to respect the directives and regulations of the European bodies. The European Commission regulation which provides for each Member State the implementation of the ESSPROS methodology which refers to the coordination of social security systems in each country in terms of statistical data collection and calculation of welfare indicators on a comparable basis may also be found among these directives. This paper aims to present and analyze the way in which Romania joined this regulation, how it applies the methodology of the European Union and especially what is the level in which our system of social protection ensures welfare of citizens compared to other systems in the European Union.